2014
DOI: 10.1002/chem.201405738
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Redox‐Active Ligand‐Assisted Nitrene‐Group Transfer in a ZrIV Complex: Direct Ligand‐to‐Ligand Charge Transfer Preferred

Abstract: The mechanism of the nitrene-group transfer reaction from an organic azide to isonitrile catalyzed by a Zr(IV) d(0) complex carrying a redox-active ligand was studied by using quantum chemical molecular-modeling methods. The key step of the reaction involves the two-electron reduction of the azide moiety to release dinitrogen and provide the nitrene fragment, which is subsequently transferred to the isonitrile substrate. The reducing equivalents are supplied by the redox-active bis(2-iso-propylamido-4-methoxyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
(89 reference statements)
1
10
0
Order By: Relevance
“…Recently, a detailed DFT computational study regarding the mechanism of this nitrogen group-transfer reaction was reported by the Baik group. 31 This study nicely supports the mechanism proposed by Heyduk, as electron transfer from the NNN ligand to the azido substrate was found to be energetically favoured over the classic metal-to-substrate electron transfer pathway. However, the calculated pathway to convert 16 into imido species 17 involves several intermediates.…”
Section: Redox-active Ligands As Electron Reservoir (A) Early Transit...supporting
confidence: 88%
“…Recently, a detailed DFT computational study regarding the mechanism of this nitrogen group-transfer reaction was reported by the Baik group. 31 This study nicely supports the mechanism proposed by Heyduk, as electron transfer from the NNN ligand to the azido substrate was found to be energetically favoured over the classic metal-to-substrate electron transfer pathway. However, the calculated pathway to convert 16 into imido species 17 involves several intermediates.…”
Section: Redox-active Ligands As Electron Reservoir (A) Early Transit...supporting
confidence: 88%
“…5 and more recent scaffolds. [73][74][75] It is even potentially applicable to ligands with longer unsaturated tethering chains, such nacnac or acac (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, Cummins et al used kinetic measurements and crossover experiments to propose that their V III azide adduct extrudes N 2 in a second-order process. More recently, Hall et al used DFT methods to demonstrate that Abu-Omar et al’s Re V oxo complexes traverse {Re­(α-N 3 R)} adducts when converting to the corresponding Re VII oxoimide products. , Finally, Baik and Ghosh identified a {Zr­(α,β-N 3 R)} intermediate in nitrene transfer catalysis . In view of these distinct pathways, we studied the conversion of 3 to 4 by 1 H NMR spectroscopy, using Si­(SiMe 3 ) 4 as an internal reference.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Although a transition state was not identified, the microscopic reverse of this process has a thermodynamic driving force of 33.7 kcal mol –1 ( vide infra , Figure ), which well surpasses the experimental barrier for deazotation. Second, Hillhouse et al’s isolation of {Ni­(β,γ-N 3 R)} adducts coupled with the viability of Baik and Ghosh’s {Zr­(α,β-N 3 R)} computed intermediate suggests that N 2 extrusion could occur via initial slippage of the azide ligand to generate η 2 -N 3 Ad isomers of 3 (Figure , red dashed line). In fact, this leads to a [(Tp t Bu,Me )­TiCl­(β,γ-N 3 Ad)] intermediate ( 3 β,γ ) at slightly higher energy than 3 (7.0 kcal mol –1 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation